(untitled) (Journal of Philosophy Culture and Political Science, 2018)
XX century The atheistic interpretation of the Bolsheviks who came to power by revolutionary revolution in the Russian Empire in the first half of the year, and their scientific concepts were based on the materialistic view formed negative conclusions and concepts in Soviet science. For example, religion is anti-cultural, the eradication of ancient religious traditions, extensive propaganda of atheistic propaganda as an instrument against it, the core of culture and spirituality is a radical rejection of the worldrecognized religion, its misunderstanding of humanity, humanity, instead of any roots. The main purpose of the party was to educate a new communist society and a new atheist person. As a result, the USSR has developed a history of uncultivated history and secular socialist culture. Today, the idea of religion is not exist has come to an end. There is no soviet Soviet government. After gaining freedom of thought from the people who were free from political strife, religious inquiries were made in public consciousness. Place and place of religion in the field of social sciences; the use of moral values of different religions in public education; the issues related to the principles of relations between religious associations and the state were considered. There is a great need for a real answer to the questions of multinational and multi-religious Kazakhstan. Key words: USSR, People’s Commissariat of Education (EAC), All-Union Executive Committee (OAS), Central Committee of the Communist (Bolshevik) Party of Russia, National Commissariat for Nationalities.